2005
DOI: 10.1007/s10620-005-2777-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Polyethylene Glycol and Celecoxib on Colonic Aberrant Crypt Foci and Tumors in F344 Rats

Abstract: We investigated whether celecoxib augments the protective effect of polyethylene glycol (PEG) on colonic aberrant crypt foci (ACF) and tumor formation in F344 rats treated with azoxymethane (AOM). Three groups of rats received AOM: I (AOM alone), II (PEG), and III (PEG/celecoxib). PEG reduced the mean number of total ACF per colon from 190 to 141 (P < 0.05; 26% reduction) and > or = 4-crypt ACF from 95 to 58 (P < 0.01; 39%). Group III rats had a greater proportion of their ACF distally; whereas transverse colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…is mediated, at least partly, by suppression of epithelial proliferation (16,19). PEG markedly reduced BrdUrd incorporation in both the ACF and the uninvolved mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…is mediated, at least partly, by suppression of epithelial proliferation (16,19). PEG markedly reduced BrdUrd incorporation in both the ACF and the uninvolved mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain its pathophysiology, such as chronic inflammation, recurrent infections 3 , pH changes, nitrosamine production by bacteria, and genetic instability of the anastomotic areas 4 , among other cases, but there are many variables that have not been uncovered. Various authors have reported the inhibitory effect of celecoxib on ACF 6 . The inhibition and reduction of COX-2, NFkβ and interleukins in rats and the protection of bone marrow cells subjected to chemical carcinogenesis in different organs have been observed by various authors 7,8 .…”
mentioning
confidence: 99%
“…Finally, increased colonic proliferation has been considered an early biomarker of increased colon cancer susceptibility (23). Previous studies reported decreased tumor development during PEG treatment in different mouse and rat models of colon cancer (8,12,32). A population-based study in patients undergoing colonoscopy showed a lower prevalence of colorectal tumors in PEG4000 users (13).…”
Section: Discussionmentioning
confidence: 87%